A participação de atletas trans no voleibol: analisando os discursos de técnicos e atletas - Lopes, Diego Trindade (2021)
Transsexual people presence in sports competitions is still strange and has been arousing the interest of different areas. Although much is said about the subject, there is still a significant lack of studies that can scientifically support these discourses. In an attempt to expand the discussion and the number of studies in the area, this study aims to understand the arguments used by technicians; cisgender and transsexual volleyball athletes to legitimize or delegitimize the participation of transsexual athletes in sports competitions of the modality. This research is qualitative, field and descriptive. Twelve people participated, 4 trans athletes; 5 cisgender athletes and 3 sports coaches, who were selected through the chain reference. In order to raise elements of analysis for the study, we used a semi-structured interview. The analysis was based on Foucault's discourse analysis in order to understand how power practices are linked to discourses in order to produce truth effects. The present investigation led to the construction of two original articles. The first aims to analyze the experience of trans athletes in sports competitions of the modality. The results revealed that there is inclusion and exclusion within the category according to the competition; similarly, there is a discrepancy in the way athletes were treated in competitions with cases of inclusion, transphobia and subjection; testosterone is used as a central argument to seek to justify the legitimation and delegitimation discourses. The second article aimed to understand the position of cisgender volleyball coaches and athletes regarding the participation of transsexual people in sports competitions. The results show that there is no consensus among the interviewed coaches and athletes on the topic addressed, with favorable positions supported by scientific studies and social aspects of sport, and opposite positions based on biological aspects.